2015
DOI: 10.17860/efd.33313
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Dönem: Anne Baba Tutumları

Abstract: Öz: Bu çalışmanın amacı 4-6 yaş aralığında çocuğu olan anne babaların ebeveynlik tutumlarını incelemektir. Çalışmada açıklayıcı karma yöntem kullanılmış; bu nedenle de ilk olarak nicel veriler toplanmış, ardından nicel verilerin açıklanması için nitel veriler toplanmıştır. Veri toplama sürecinde öncelikle 258 anne-babaya Ebeveyn Tutum Ölçeği (ETÖ) uygulanmış, sonrasında ise bu annebabalardan 20'si ile görüşmeler yapılmıştır. Nicel verilerin analizinde bağımsız örneklemler için t testi ve tek faktörlü ANOVA kul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 10 publications
1
10
0
2
Order By: Relevance
“…Sociocultural perspectives of contemporary early childhood emphasise the significance of familial relationships, particularly parent-child relationships (Edwards, 2003;Nolan and Raban, 2015), on young children's social and emotional development (Rose at al., 2018). Meanwhile, parent-child relationships are subject to various factors, including child's birth order, prenatal experiences, number of children, child's personal characteristics, family relationships and the perceived value of the child (Sak et al, 2015;Sidebotham and ALSPAC Study Team, 2001). These factors affect parental attitudes and influencing the quality of the parent-child relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Sociocultural perspectives of contemporary early childhood emphasise the significance of familial relationships, particularly parent-child relationships (Edwards, 2003;Nolan and Raban, 2015), on young children's social and emotional development (Rose at al., 2018). Meanwhile, parent-child relationships are subject to various factors, including child's birth order, prenatal experiences, number of children, child's personal characteristics, family relationships and the perceived value of the child (Sak et al, 2015;Sidebotham and ALSPAC Study Team, 2001). These factors affect parental attitudes and influencing the quality of the parent-child relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, however, the same study by İnci and Deniz (2015) found that children's genders and ages did influence the parenting attitudes of the fathers of first graders. And other researchers have found statistically significant differences in the parenting attitudes of mothers according to their children's genders (Şanlı and Öztürk, 2012), and in the parenting attitudes of parents of both genders according to their children's genders, numbers, and/or ages (Rosen, Cheever and Carrier, 2008;Sak, Şahin-Sak, Atli and Şahin, 2015) and/or their own genders or ages (Kashahu (Xhelilaj), Dibra, Osmanaga and Bushati, 2014;Lin and Billingham, 2014;Stephens, 2009). The current study also found statistically significant differences in all four parenting attitudes across parental-education levels: for instance, the mean authoritativeness scores of universityeducated respondents were higher than the authoritativeness scores of those who had only attended primary school, or not attended school.…”
Section: Discussionmentioning
confidence: 93%
“…The present study's findings showed that there were no significant differences in parenting attitudes based on the respondents' genders or ages or the ages, genders or numbers of their children, but there were significant differences according to their educational levels, house types and monthly incomes, partially echo prior studies' results. For instance, Kashahu (Xhelilaj), Dibra, Osmanaga and Bushati ( 2014) and Sak, Şahin-Sak, Atli and Şahin (2015) reported that parenting attitudes were related to parents' educational levels; and İnci and Deniz (2015) found that the parenting attitudes of the fathers of preschoolers were not influenced by the genders, ages or numbers of their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their approaches toward their children are sincere, supporting and reassuring, respectful, and loving (Taner-Derman and Başal, 2013). Authoritarian attitude is the most unhealthy one among attitudes of mother and father (Sak, Şahin-Sak, Atli and Şahin, 2015). Mothers and fathers having this attitude adopt aa strict, prescriptive and punitive approach.…”
Section: Summary Introductionmentioning
confidence: 99%